The regulatory role of m6A methylation modification in metabolic syndrome pathogenesis and progression - Ye, Diwen; Zhang, Yongjiao; Zhang, Bingyang; Liu, Junjun; Wei, Tianshu; Lu, Sumei (Frontiers in Physiology, 2024)
Metabolic syndromes are characterized by various complications caused by disrupted glucose and lipid metabolism, which are major factors affecting the health of a population. However, existing diagnostic and treatment strategies have limitations, such as the lack of early diagnostic and therapeutic approaches, variability in patient responses to treatment, and cost-effectiveness. Therefore, developing alternative solutions for metabolic syndromes is crucial. N6-methyladenosine (m6A) is one of the most abundant modifications that determine the fate of RNA. m6A modifications are closely associated with metabolic syndrome development and present novel prospects for clinical applications. Aberrant m6A modifications have been detected during inflammatory infiltration, apoptosis, autophagy, iron sagging, necrosis, and scorching during metabolic syndrome pathogenesis and progression. However, few reviews have systematically described the correlation between m6A modifications and these factors concerning metabolic syndrome pathogenesis and progression. This study summarizes the m6A methylation regulators and their roles in metabolic syndrome development, highlighting the potential of m6A modification as a biomarker in metabolic disorders.